A Manual for Writers of Research Papers, Theses, and Dissertations: Chicago Style for Students and Researchers - Turabian, Kate L. (Chicago University of Chicago Press, 2007)
Dewey, Bellow, Strauss, Friedman--the University of Chicago has been the home of some of the most important thinkers of the modern age. But perhaps no name has been spoken with more respect than Turabian. The dissertation secretary at Chicago for decades, Kate L. Turabian literally wrote the book on the successful completion and submission of the student paper. Her Manual for Writers of Research Papers, Theses, and Dissertations, created from her years of experience with research projects across all fields, has sold more than seven million copies since it was first published in 1937. Now, with this seventh edition, "Turabian's Manual" has undergone its most extensive revision, ensuring that it will remain the most valuable handbook for writers at every level--from first-year undergraduates, to dissertation writers apprehensively submitting final manuscripts, to senior scholars who may be old hands at research and writing but less familiar with new media citation styles. Gregory G. Colomb, Joseph M. Williams, and the late Wayne C. Booth--the gifted team behind The Craft of Research--and the University of Chicago Press Editorial Staff combined their wide-ranging expertise to remake this classic resource. They preserve Turabian's clear and practical advice while fully embracing the new modes of research, writing, and source citation brought about by the age of the Internet.